'Appropriate'ing grief: mothers, widows and the (un) grievability of military death. Issue 1 (2nd January 2022) - Rashid, Maria
ABSTRACT : The article interrogates the grievability of military lives by studying female next of kin as subjects of the post-colonial Pakistan military and suggests that these non-masculine and non-military bodies act as a symbolic embodiment of grief associated with soldier death, and as its material benefactor. A study of their affective and material management, the article traces national and local commemorative practices of grief around soldier death instituted by the Pakistan Military during the War on Terror. Female bodies are conscripted in the war effort, as dependents whose destructive affect needs restraint and channelling into appropriate grief, and as vital resources whose excessive affect can be harnessed to express productive grief and support for unpopular war policy. Drawing on fieldwork in villages, analysis of military commemorations, and interviews with officers and female next of kin, the article traces the overwhelming sense of loss that refuses closure within militarised grieving rituals. It concludes that the surfeit of public and collective grief around military lives paradoxically renders these deaths ungrievable.